Global hotspots and trends in tea anti-obesity research: a bibliometric analysis from 2004 to 2024 - Liu, Shan; Fan, Boyan; Li, Xiaoping; Sun, Guixiang (Frontiers in Nutrition, 2024)
Background: The prevalence of obesity and its related ailments is on the rise, posing a substantial challenge to public health. Tea, widely enjoyed for its flavors, has shown notable potential in mitigating obesity. Yet, there remains a lack of exhaustive bibliometric studies in this domain. Methods: We retrieved and analyzed multidimensional data concerning tea and obesity studies from January 2004 to June 2024, using the Web of Science Core Collection database. This bibliometric investigation utilized tools such as Bibliometrix, CiteSpace, and VOSviewer to gather and analyze data concerning geographical distribution, leading institutions, prolific authors, impactful journals, citation patterns, and prevalent keywords. Results: There has been a significant surge in publications relevant to this field within the last two decades. Notably, China, Hunan Agricultural University, and the journal Food and Function have emerged as leading contributors in terms of country, institution, and publication medium, respectively. Zhonghua Liu of Hunan Agricultural University has the distinction of most publications, whereas Joshua D. Lambert of The State University of New Jersey is the most cited author. Analyses of co-citations and frequently used keywords have identified critical focus areas within tea anti-obesity research. Current studies are primarily aimed at understanding the roles of tea components in regulating gut microbiota, boosting fat oxidation, and increasing metabolic rate. The research trajectory has progressed from preliminary mechanism studies and clinical trials to more sophisticated investigations into the mechanisms, particularly focusing on tea's regulatory effects on gut microbiota. Conclusion: This study offers an intricate overview of the prevailing conditions, principal focus areas, and developmental trends in the research of tea’s role against obesity. It delivers a comprehensive summary and discourse on the recent progress in this field, emphasizing the study’s core findings and pivotal insights. Highlighting tea's efficacy in obesity prevention and treatment, this study also points out the critical need for continued research in this area.